2017
DOI: 10.19082/4746
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes toward brain death and organ donation in Bojnurd

Abstract: BackgroundOrgan donation in Iran is common. Bojnurd (North Khorasan, Iran) is a multi-ethnic city, and people with different religions and cultures live together and that could be associated with their behavior and attitude towards health-related issues. So far, no study has taken place on brain death and organ donation in the province of North Khorasan.ObjectiveThe aim of this study was to determine the knowledge and attitudes of citizens of Bojnurd toward brain death and organ donation.MethodsThis cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…This is consistent with previous findings, where less than half of the participants surveyed demonstrated an adequate understanding of brain death and organ donation [ 15 ]. However, this finding differs from the results of two studies conducted in Turkey and Iran that indicated inadequate awareness and a necessity to enhance the understanding of brain death and organ donation [ 16 , 17 ]. Furthermore, numerous studies have investigated the awareness of organ donation and brain death among various groups in the Kingdom of Saudi Arabia, including university and secondary school students in the southern and Al-Ahsa regions [ 18 - 20 ].…”
Section: Discussioncontrasting
confidence: 96%
“…This is consistent with previous findings, where less than half of the participants surveyed demonstrated an adequate understanding of brain death and organ donation [ 15 ]. However, this finding differs from the results of two studies conducted in Turkey and Iran that indicated inadequate awareness and a necessity to enhance the understanding of brain death and organ donation [ 16 , 17 ]. Furthermore, numerous studies have investigated the awareness of organ donation and brain death among various groups in the Kingdom of Saudi Arabia, including university and secondary school students in the southern and Al-Ahsa regions [ 18 - 20 ].…”
Section: Discussioncontrasting
confidence: 96%
“…Those with negative outlooks also had lower levels of awareness, and this was a statistically significant finding (p=0.047). This led them to the conclusion that most people have an unfavorable view of organ donation (Hejazi et al 2017) [9] . This research on organ donation awareness was carried out at one of Guwahati's top educational institutions.…”
Section: Resultsmentioning
confidence: 99%
“…23 26 This inconsistent understanding of the ethical and scientific basis of brain death begins to explain the wide variability seen in how brain death protocol is performed around the country. 27 Similar studies demonstrate a lack of consensus in attitude and protocol outside the US as well 28 31 …”
Section: Introductionmentioning
confidence: 95%